2011
DOI: 10.1038/onc.2011.286
|View full text |Cite
|
Sign up to set email alerts
|

New pyrazolo[3,4-d]pyrimidine SRC inhibitors induce apoptosis in mesothelioma cell lines through p27 nuclear stabilization

Abstract: Malignant mesothelioma (MM) is a highly aggressive tumor of the serous membranes for which there is currently no effective curative modality. Recent data suggest that hyperactivation of the tyrosine kinase SRC has a key role in MM development and therefore this kinase represents an important molecular target for MM therapy. We tested new pyrazolo [3,4-d]pyrimidine SRC inhibitors on a panel of MM cell lines expressing the active form of SRC. These SRC inhibitors exerted a significant proapoptotic effect on MM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 49 publications
(54 reference statements)
8
39
0
Order By: Relevance
“…This difference in effectiveness is likely to be dependent on a different membrane penetration of the compounds in diverse cell lines, as previously suggested. 35,13 To date, several small molecules targeting SRC have been developed. 12 In the present study, we compared the effectiveness of our compounds with that of the wellknown SRC inhibitor PP2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference in effectiveness is likely to be dependent on a different membrane penetration of the compounds in diverse cell lines, as previously suggested. 35,13 To date, several small molecules targeting SRC have been developed. 12 In the present study, we compared the effectiveness of our compounds with that of the wellknown SRC inhibitor PP2.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that our SRC inhibitors do not affect non-neoplastic cells derived from different tissues, 13,38,41 since these compounds are effective only on cancer cells expressing the active form of SRC. Moreover, it has been shown that G 2 /M checkpoint abrogators, including WEE1 inhibitors, can selectively sensitize cancer cells to anticancer agents without affecting non-cancerous cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pyrazolo [3,4-d]pyrimidine nucleus is considered as an isostere to the purine nucleus and hence exhibits promising antiproliferative activities. Several members of this family were found to induce apoptosis and/or reduce cell proliferation in many cancer cell lines such as breast, colon, lung and liver cell lines [9][10][11][12][13][14][15][16][17] . Different mechanisms account for the cytotoxic effect of this class of compounds, where they have been reported to act as inhibitors of different enzymes such as CDK 2 14 , epidermal growth factor 15 , Src or dual Src/AbI inhibitors the synthesis of anti-tumor agents.…”
Section: Introductionmentioning
confidence: 99%